Retirement in the 21st century - Daniel Chandler; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2014)
Since 1995, employment rates of men in their 50s and 60s have steadily increased, following a long period of decline from the late 1960s. At the same time, employment rates of older women have continued to increase. This growth in employment rates was only somewhat arrested during the recent recession. This report looks at the factors that have contributed to this growth in employment rates and, in particular, what might explain the turnaround in the trend for older men in the mid-1990s. We survey the recent literature and present a new analysis of data from the English Longitudinal Study of Ageing, which covers the period from 2002-03 to 2012-13. In this report, we distinguish between factors affecting mainly the demand for older workers and those affecting mainly the supply of older workers. However, in practice, it is very difficult to disentangle the effects of the two.
Keywords: 330